Risk factors for pneumothorax in advanced and/or metastatic soft tissue sarcoma patients during pazopanib treatment: a single-institute analysis - Nakano, Kenji (BMC Cancer, 2016)
BACKGROUND: After the approval of pazopanib for the treatment of soft tissue sarcoma (STS), pneumothorax was reported as an unexpected adverse event during pazopanib treatment. The incidence and risk factors of pneumothorax during pazopanib treatment for STSs have not been established yet. METHODS: We retrospectively reviewed the cases of all of the STS patients treated with pazopanib between November 2012 and December 2014 at our institute and evaluated the prevalence, incidence, treatment details and risk factors for pneumothorax in the STS patients during pazopanib treatment. RESULTS: A total of 58 patients were enrolled; 45 of them had lung and/or pleural lesions at the start of pazopanib treatment. During the median follow-up time of 219 days (range 23–659), 13 pneumothorax events occurred in six patients; the prevalence and incidence of pneumothorax were 10.3 % and 0.56 per treatment-year, respectively. The median onset of pneumothorax was day 115 (range 6–311). No patients died of pneumothorax, but pazopanib was interrupted in 10 events and chest drainage was performed in eight events. Pazopanib continuation or restart after the recovery from pneumothorax was conducted after 9 of the 13 events. The median progression-free survival of patients with and without pneumothorax events were 144 and 128 days (p = 0.89) and the median overall survival periods were 293 and 285 days (p = 0.69), respectively. By logistic regression analyses, the maximum diameter of the lung metastases ≥ 30 mm (OR 13.3, 95 % CI 1.1–155.4, p = 0.039) and a history of pneumothorax before the pazopanib induction (OR 16.6, 95 % CI 1.1–256.1, p = 0.045) were significantly predictive of pneumothorax. CONCLUSIONS: In our retrospective analysis, pneumothorax was observed in 10.3 % of 58 STS patients during pazopanib treatment. The diameter of the lung metastases and a history of pneumothorax could be useful for evaluating the risk of pneumothorax in pazopanib treatment.